Strategi Dakwah Majelis Taklim ‘Aisyiyah dalam Membentuk Karakter Muslimah Berkemajuan: Studi Kualitatif di Pimpinan Cabang Medan Perjuangan - Sidiq Sudarto; Naufal Akbar Batubara; Fadillah Ihwani; Muhammad Nurul Habib; Siti Aisyah Lubis; Hendra Kurniawan (Medan Resource Center, 2025)
This study examines the da‘wah strategy implemented by the ‘Aisyiyah Majelis Taklim in shaping the character of progressive Muslim women at the Branch Leadership of ‘Aisyiyah Medan Perjuangan. This research is motivated by the need for contextual and transformative da‘wah approaches that respond to contemporary religious, social, and moral challenges faced by Muslim women. The study aims to analyze planning, implementation, and media utilization of da‘wah strategies at the branch level. This research employed a qualitative descriptive method, involving key subjects such as branch administrators, muballighah, and members of the congregation. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed thematically to capture patterns of strategy and character formation. The findings show that da‘wah strategies at the branch level are systematically designed based on congregational needs, implemented through dialogical and participatory methods, and strengthened by the use of community-based and digital media. The novelty of this study lies in highlighting how da‘wah strategies at the ‘Aisyiyah branch level function as a grassroots model of progressive da‘wah that effectively contributes to strengthening religious awareness, moral integrity, and social responsibility among Muslim women.